2021
DOI: 10.1002/mnfr.202000859
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Pork Induces Disorders of Glucose Metabolism in Mice

Abstract: Scope Consumption of red meat, particularly processed red meat, has been reported to be associated with type 2 diabetes risk, and oxidized proteins and amino acids may be involved in this process. This study explores the effects of pork with varying degrees of oxidative injury caused by cooking on glucose metabolism in mice. Methods and results Cooked pork is freeze‐dried to prepare animal feed. Mice are fed either a control diet (CON), a low‐ (LOP), or a high‐oxidative injury pork diet (HOP) for 12 weeks. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Thereafter, we examined the effects of MR on pancreatic β-cell fate and function in HFD-induced obese mice. In vitro , we discovered that MR reduced β-TC6 apoptosis caused by PA. Bcl-2 is an anti-apoptotic protein, and Bax and Caspase-3 are pro-apoptotic factors . In this study, MR inhibited the low expression of Bcl-2 and the high expression of Bax and caspase-3 in mice pancreas induced by HFD and β-TC6 cells induced by PA.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, we examined the effects of MR on pancreatic β-cell fate and function in HFD-induced obese mice. In vitro , we discovered that MR reduced β-TC6 apoptosis caused by PA. Bcl-2 is an anti-apoptotic protein, and Bax and Caspase-3 are pro-apoptotic factors . In this study, MR inhibited the low expression of Bcl-2 and the high expression of Bax and caspase-3 in mice pancreas induced by HFD and β-TC6 cells induced by PA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a strong link between protein oxidation and age-related diseases, such as diabetes, atherosclerosis, and neurodegenerative diseases (Davies & Dean, 1997). For example, Ge et al (2021) showed that the intake of oxidized pork induces disorders of glucose metabolism in mice by impairing pancreatic insulin secretion.…”
Section: Nutrition and Healthmentioning
confidence: 99%
“…To similar conclusions came Ge et al ( 2020 ) who found that the alteration of the gut microbiota in mice by the intake of oxidized pork contributed to the onset of oxidative stress and inflammation processes in this murine model. The same authors reported that dietary oxidized pork induced impaired lipid metabolism by decreasing insulin levels and suppressing of the insulin receptor substrate-1 (IRS-1)/phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway and its downstream signaling molecules (Ge et al 2021 ). Li et al ( 2019 ) observed impaired spatial learning and memory in rats fed with carbonylated proteins from a severely processed milk product.…”
Section: Concise Update On the Biological Consequences Of Protein Car...mentioning
confidence: 99%